Exploration of the innovative talent training model for Chinese-Foreign cooperative education in Chinese universities in the post-epidemic ERA - Zhao, Na; AZIZ, NORZAH BINTI ABDUL (Edelweiss Applied Science and Technology, 2025)
This research examines the effect of Chinese–foreign cooperative education models, with an emphasis on Innovative Training Models (ITM), Teaching Quality (TQ), and Epidemic Influence (EI) on student academic performance (SAP). A broad demographic picture was presented on 500 students, 100 faculty members, and 20 administrative staff located in 30 provinces. The average GPA of students was reported, the graduation rate was 85 percent, which occurred after graduation, and the employment rate after six months of graduation was 78 percent. Results of multiple regressions indicated that ITM (β = 0.45, p < 0.001) and TQ (β = 0.37, p < 0.001) had positive significant effects on SAP, while EI had a negative effect (β = -0.22, p < 0.05). Results of the Sobel test (Z = 4.12, p < 0.001) indicated that TQ mediated the relationship between ITM and SAP. It was found that EI moderated the influence of ITM on SAP (β = 0.15; p = 0.034). Key themes were developed for the use of cooperative education that, in the context of the above, could be characterized as flexibility, technological integration, and policy support. The findings identified here are of great value for enhancing educational practices and strategies to successfully meet external disruptions such as the global COVID-19 pandemic.